2009
DOI: 10.14267/veztud.2009.06.05
|View full text |Cite
|
Sign up to set email alerts
|

The influence of speed of integration on M&A integration Success

Abstract: Despite the importance of the dimension of time in the world of competitive strategy, only a few researches have focused on the issue of the speed of the integration (SOI) in the process of merger/acquisition (M&A) and its impact on the deal-success. This article focused on the issue of speed of integration and its impact on the integration effectiveness and the success of the M&A. This impact changes depending on the combination of a number of variables such as the main reason of the acquisition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It is suggested that both the motives behind this activity and post‐acquisition organizational changes are driven by synergistic factors (Thompson et al , 1992) Because operational synergies promise to improve competitiveness in terms of lower cost or greater product differentiation, we speculate that these synergies are the most difficult ones to realize and will potentially result in another wave of divestitures. Despite the importance of the dimension of time in the world of competitive strategy, only a few researchers have focussed on the issue of the speed of the integration in the process of M&A and its impact on the deal success (Morga and Barakonyi, 2009). The pharma and biotech industry has faced major challenges in the previous years with respect to both the revenues and costs which led to a merger wave in this particular sector (Kirchhoff and Schiereck, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is suggested that both the motives behind this activity and post‐acquisition organizational changes are driven by synergistic factors (Thompson et al , 1992) Because operational synergies promise to improve competitiveness in terms of lower cost or greater product differentiation, we speculate that these synergies are the most difficult ones to realize and will potentially result in another wave of divestitures. Despite the importance of the dimension of time in the world of competitive strategy, only a few researchers have focussed on the issue of the speed of the integration in the process of M&A and its impact on the deal success (Morga and Barakonyi, 2009). The pharma and biotech industry has faced major challenges in the previous years with respect to both the revenues and costs which led to a merger wave in this particular sector (Kirchhoff and Schiereck, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies search incessantly for new business models and business strategies that will improve qualities, as fast as possible, so that they can respond in the best possible way to the changing demand of the clients and to the changes in the map of competition in the domain (Morag & Barakonyi, 2009). When corporate governance considers types of strategies appropriate for company -one option is the growth strategy.…”
Section: Mergers and Acquisitionsmentioning
confidence: 99%
“…In external growth, the company is aided by the resources and abilities of other companies and this synergy can significantly improve the company` s competitive ability. Thus, the strategy of M&As is one of the main strategies adopted by companies and corporations so as to expand into new markets, diversify products and services, and increase the competition in the field (Morag & Barakonyi, 2009) Growth through M&A include (Montanari, Morgan & Bracker, 1990):…”
Section: Mergers and Acquisitionsmentioning
confidence: 99%
See 2 more Smart Citations